ANALISIS DAYA SAING EKSPOR MINYAK SAWIT INDONESIA DAN MALAYSIA DI PASAR INTERNASIONAL - Hagi '; Syaiful Hadi; Ermi Tety (PEKBIS, 2013)
The purpose of this research is to analyze dynamics export competitiveness ofIndonesia’s and Malaysia’s palm oil in International market. And to analyze exportperformance of Indonesia’s and Malaysia’s palm oil in International market. The dataused in the study was time series of 1995 - 2009 obtained from various sourcessuch as FAO, MPOB, BPS, Dirjenbun Deptan, and Oil World. The result of thisresearch are, dynamic export competitiveness of Indonesia’s palm oil haveimprovement in exporting market of palm oil in the world, especially in Asian andEurope, except in case of palm oil in some Europe state. Effect of standard growthIndonesia and Malaysia have positive value. Indonesia’s palm oil more competitivecompared by Malaysia in Asian, but in Europe, Malaysia’s palm oil more competitivecompared by Indonesia. This matter is shown by negative value from effect ofmarket distribution and effect of residual. Competitiveness of Indonesia andMalaysia for palm oil product can be told above average of the world, because theindex RCA more than one. Then, the value of ratio net Export and Total TradeIndonesia and Malaysia also showed a positive value which means that Indonesiaand Malaysia is an exporter of palm oil.Keywords:Palm oil export, constant market share, revealed comparativeadvantage.